Gray Matter Alterations Associated With Dissociation in Female Survivors of Childhood Trauma - Daniels, Judith K.; Schulz, Anna; Schellong, Julia; Han, Pengfei; Rottstädt, Fabian; Diers, Kersten; Weidner, Kerstin; Croy, Ilona (Frontiers in Psychology, 2019)
Objective: Across various axis-1 disorders, the severity of dissociative symptoms is significantly related to a history of childhood traumatization. Thus, the question arises if coping with childhood trauma leads to neural adaptations that enhance the frequency of dissociative processing during adulthood. The aim of the two reported studies therefore was to identify and replicate grey matter alterations associated with dissociation. Methods and Results: In a first study, whole-brain MRI data were acquired for 22 female in-patients with trauma-spectrum disorders and a history of severe childhood trauma. Voxel-based morphometry (VBM) was carried out to test for significant correlations between dissociation (depersonalization/derealisation) severity and grey matter volume. Dissociation severity was positively associated with volume in the left angular gyrus. This result was diagnosis-invariant. The replication study involved 26 female in-patients with trauma-spectrum disorders and 25 healthy controls. No significant association between dissociation severity and brain volume in a left angular gyrus region of interest located at the peak identified in study 1 was identified and no significant group difference in this region could be established. Conclusion: The angular gyrus has previously been implicated in the processing of agency and vestibular integration as well as dissociative processing. The current attempt at a direct replication of brain volume alterations however failed. The data thus only partially support the notion that dissociative processing is associated trans-diagnostically with structural brain alterations in the left angular gyrus and independent replication in a larger patient sample is essential.